Graphene and carbon nanodots in mesoporous materials: an interactive platform for functional applications. Issue 30 (15th July 2015) - Innocenzi, Plinio; Malfatti, Luca; Carboni, Davide
Abstract : This review is focused on a specific class of nanocomposites obtained through combined assembly of graphene or carbon-based nanomaterials and mesoporous inorganic or hybrid materials. Abstract : The present review is focused on a specific class of nanocomposites obtained through integration of graphene or carbon-based nanomaterials (such as carbon nanodots) with mesoporous inorganic or hybrid materials, obtained via template assisted self-assembly. The task of integrating graphene and carbon nanodots with a self-assembly process is still very challenging and this review shows some of the solutions which have been envisaged so far. These nanocomposite materials are an ideal interactive platform for developing innovative functional applications; they have a high capability of undergoing integration into advanced devices, which well exploits the advantage of tuning the wide properties and flexibility of the soft-chemistry route. A wide range of applications have been developed so far which span from sensing to electronics up to optics and biomedicine. Even though a large number of proof-of-concepts have been reported to date, an even greater expansion of applications in the field is expected to happen in the near future.